Chronic Consumption of a Commercial Energy Drink Reduces Blood Pressure in Normotensive Wild-Type Mice - Graneri, Liam; D'Alonzo, Zachary; Lam, Virginie; Mamo, John; Dhaliwal, Satvinder; Takechi, Ryusuke (Frontiers in Nutrition, 2019)
Objective: Studies report that acute consumption of energy drinks transiently increases blood pressure (BP). However, few studies report the effect of chronic energy drink consumption on BP. In this study, we investigated the effects of long-term energy drink ingestion on BP in C57BL/6J normotensive wild-type mice. Research Methods and Procedures: Groups of mice were randomized to no treatment (water) (Control group), or to Mother™ provided as a decarbonated 30% (v/v) drinking solution (Energy Drink group), sugar-free Mother™ at 30% (Sugar-free group), Coca Cola™ at 30% (Coke group) for a total intervention period of 13 weeks. Results: After 13 weeks of intervention, the control mice showed a modest increase in SBP, DBP, and MAP by 7.18.8, 5.89.4, and 6.39.1 mmHg, respectively. However, the Energy Drink significantly decreased the DBP and MAP by 18.89.9 and 15.39.8 mmHg, respectively. Similarly, Sugar-free group mice showed significant decrease of the SBP, DBP, and MAP by 10.855.6, 18.76.7, and 15.66.1 mmHg, respectively. The SBP, DBP and MAP in Coke mice showed no significant changes. The estimated cumulative intake of caffeine, taurine, and vitamin B3 and B5 was significantly higher in the mice of Energy Drink and Sugar-free groups compared to the Control and Coke mice. Conclusion: Collectively, the data suggest that the long-term chronic consumption of energy drinks may significantly lower the BP in normotensive mice through the actions of caffeine, taurine, and/or B-vitamins. The study findings do not support consideration of energy drinks for BP management, but rather demonstrate no long-term amplification of BP in normotensive preclinical models.